Optimizing Adhesion of Orthodontic Brackets to Fluorosed Teeth - Ion Lupan; Sachin Sachdev; Eyad Sannoufi (Romanian Society of Oral Rehabilitation, 2011)
Introduction: Bonding of orthodontic brackets to fluorosed enamel is a challenge for all dental clinicians. The objective of this study was to determine the success of bracket retention in patients with dental fluorosis using a different acid etch protocol. Methods: 12 patients with varying degrees of dental fluorosis were bonded in vivo with a split mouth design with one side of the arch treated with 37% phosphoric acid for 60 seconds and then bonded. The other side of the arch in all patients was pretreated with Opalustre (ultradent) containing 6.6 % hydrochloric acid and silicon carbide micro particles in a water-soluble paste for 45 seconds and then bonded. Results: Over a period of 12 months, 17 bond failures occurred in the side treated with 37% phosphoric acid and 7 bond failures occurred in the side treated with Opalustre containing hydrochloric acid and silicon carbide micro particles. An unpaired t test statistical analysis revealed p=.0108 which is statistically significant by conventional criteria, demonstrating the effectiveness of pretreatment of teeth with Opalustre for orthodontic bonding in cases of dental fluorosis. Conclusions: The rate of bond failure with 37% phosphoric acid is high in patients with dental fluorosis. The rate of bond failure is higher with pretreatment with phosphoric acid than with Opalustre, so Opalustre containing hydrochloric acid can be recommended for pretreatment of teeth with fluorosis for orthodontic bonding. The recommended acid etch protocol also saves chair side time of the orthodontist, improves success rate of the treatment and minimizes cost of the treatment by preventing recurrent bond failures.